Pengaruh Kompetensi dan Lingkungan Kerja berpengaruh Terhadap Kinerja Guru SMA Negeri Kuantan Hilir Provinsi Riau - Ansori, Putra Budi (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research was conducted in the research conducted at SMA Negeri 1 Kuantan Hilir, Kuantan Singingi District, jenderal Soedirman Street, Kepala Pulau, Baserah in 2019. The study aims to determine the effect of competencies and work environment on the performance of teachers in SMA Negeri 1 Kuantan Hilir. Population in this research is population in research it is a whole an teachers  of SMA Negeri 1 Kuantan Hilir, which consisted of 51 teachers. Because the population in this study is little, the authors use the entire population to be sampled. From the analysis of multiple linear regression equation was formulated:  Y= 9,236 + 0,371X1+ 0,444X2.  The results of the t test (partial test) obtained the value of t arithmetic for Competence / X1 (3,025) and Work Environment / X2 (3,992) greater than t table of 2,01063, then it has a significant effect on the teacher performance variable of SMA 1 Kuantan Hilir. F Test Results (joint test), it is concluded that  F count  is 11.923> F table 3.19 so that simultaneously   the variables of competence and work environment have a significant effect on the performance of teachers of SMA Negeri 1 Kuantan Hilir. There are contribution the influence of competencies and Work environment of the performance of teachers at SMA 1 Kuantan Hilir of Obtained value of Adjusted R Square equal to 0,304 or 30,4% and 69,6 % influenced by the other factors that are not pursuing in this research. So this research to strengthen previous studies